Study on the Fracture Behavior of Cracks Emanating from Tunnel Spandrel under Blasting Loads by Using TMCSC Specimens - Bang Liu; Zheming Zhu; Ruifeng Liu; Lei Zhou; Duanying Wan (Shock and Vibration)
Radial cracks may exist around tunnel edge, and these cracks may propagate and weaken tunnel stability under nearby blasting operations. In order to study the blast-induced fracture behavior of radial cracks emanating from a tunnel spandrel, a tunnel model containing a spandrel crack (TMCSC) with different inclination angles was proposed in this paper. Crack propagation gauges (CPGs) and strain gauges were used in the experiments to measure crack initiation moment and propagation time. Finite difference models were established by using AUTODYN code to simulate crack propagation behavior and propagation path. ABAQUS code was used to calculate dynamic stress intensity factors (SIFs). The results show that (1) crack inclination angles affect crack initiation angles and crack propagation lengths significantly; (2) critical SIFs of both mode I and mode II decrease gradually with the increase of the crack propagation speed; (3) the dynamic energy release rates vary during crack propagation; and (4) there are “crack arrest points” on the crack propagation paths in which the crack propagation speed is very small.